Antibiotic therapy of community-acquired pneumonia in children of different age groups: outcomes of a multidisciplinary team approach (a retrospective analysis) - Rafalskyi, Vladyslav; Servetnyk, Nadiia (The Ukrainian Scientific Medical Youth Journal, 2025)
Community-acquired pneumonia in children is a common infectious disease associated with a risk of severe complications. Optimisation of antimicrobial therapy is a key task, particularly with the involvement of a clinical pharmacist. The aim of this study was to evaluate the effectiveness of a multidisciplinary team, with a focus on the role of the clinical pharmacist in rationalising antimicrobial therapy for paediatric community-acquired pneumonia. A retrospective analysis of 90 cases of community-acquired pneumonia treatment in children was conducted at a clinic where a multidisciplinary team operates within the infection control unit. The analysis included the frequency of antibiotic prescriptions (considering the AWaRe classification), duration of therapy, and routes of administration of antimicrobials. Statistical analysis was performed using the χ² and t-test. The most frequently prescribed agents were cefotaxime (55.1%) and macrolides (24.4%). In the older age group, antibiotic combinations were more commonly used, which was associated with a significantly higher days of treatment burden (p<0.005). Reserve group antibiotics were not used. In 36.7% of cases, antibiotics were administered orally. The involvement of a multidisciplinary team, particularly a clinical pharmacist, contributes to improving the quality of antimicrobial therapy, minimising the unjustified use of broad-spectrum antibiotics, and ensuring adherence to the AWaRe principles and WHO recommendations.